Identifying and prioritizing human behaviors that benefit biodiversity. Issue 9 (23rd July 2020) - Selinske, Matthew J.; Garrard, Georgia E.; Gregg, Emily A.; Kusmanoff, Alexander M.; Kidd, Lindall R.; Cullen, Meghan T.; Cooper, Michelle; Geary, William L.; Hatty, Melissa A.; Hames, Fern; Kneebone, Sarah; McLeod, Emily M.; et al.
Abstract: The conservation profession is increasingly seeking effective ways to reduce societal impact on biodiversity, including through targeted behavior change interventions. Multiple conservation behavior change programs exist, but there is also great uncertainty regarding which behaviors are most strategic to target. Behavioral prioritization is a tool that has been used effectively to support behavior change decision‐making in other environmental disciplines and more recently for a small sub‐set of biodiversity behavior change challenges. Here, we use behavioral prioritization to identify individual behaviors that could be modified to achieve biodiversity benefits in the state of Victoria, Australia. We use an adapted nominal group technique method to identify potential biodiversity behaviors and, for each behavior, estimate the corresponding plasticity (or capacity for change) and positive impact on biodiversity outcomes. We elicited 27 behaviors that individuals could undertake to benefit or reduce their negative impact on biodiversity. This list was then used to prioritize 10 behaviors as determined by their likely effect(s) on biodiversity, plasticity, and current prevalence in Victoria. We take a first step in outlining a list of behaviors that can direct Victorian decision‐makers toward increasing positive and reducing negative impacts of society on biodiversity, guide motivated individuals to reduce their own biodiversity footprint, and more broadly, develop a behavior change research agenda for behaviors most likely to benefit biodiversity. Abstract :